2020
DOI: 10.1097/md.0000000000021066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fusu mixture (Wen-Shen-Qian-Yang Method) on sepsis-induced acute respiratory distress syndrome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) has shown suppressive effects on LPS-induced LPS-endothelial inflammation, including oxidative stress, cell apoptosis, microcirculatory disturbances and organ injury [10]. This protection on endothelium was validated in clinical practice on treatment of sepsis-induced acute respiratory distress syndrome [11]. Moreover, animal model showed that TCM decoction can ameliorate sepsis-induced acute lung injury, and the mechanism may be associated with decreased production of pro-inflammatory mediator by TCM decoction in LPS-pretreated HUVEC [12].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has shown suppressive effects on LPS-induced LPS-endothelial inflammation, including oxidative stress, cell apoptosis, microcirculatory disturbances and organ injury [10]. This protection on endothelium was validated in clinical practice on treatment of sepsis-induced acute respiratory distress syndrome [11]. Moreover, animal model showed that TCM decoction can ameliorate sepsis-induced acute lung injury, and the mechanism may be associated with decreased production of pro-inflammatory mediator by TCM decoction in LPS-pretreated HUVEC [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main components in the decoction included ginseng, honeysuckle, rhubarb, dandelion, wild chrysanthemum, and so on. The existing pharmacology confirmed that ginseng has the effect of regulating immune function and the neuroendocrine system (19); honeysuckle is a good medicine for clearing away heat and toxic substances, which can remove endotoxin and improve the body's immunity (8); wild chrysanthemum and dandelion can sterilize, having the effect of detoxification and diuresis (11); rhubarb helps to repair intestinal microecology, inhibit bacterial reproduction, and improve gastrointestinal function, thereby reducing inflammation (13). A study (14) used acupuncture to stimulate specific acupoints, improving the immunity of sepsis patients and improving clinical treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelial cells (VECs) play a role in regulating vascular permeability, vascular tone, and blood flow [ 6 ]. Its mechanisms include forming new blood vessels by proliferating, migrating, differentiating, and maintaining microvascular integrity and blood flow via anti-inflammatory, antithrombotic, and vasodilatory activities [ 7 , 8 ]. Nonetheless, mature VECs are limited by such defects as low activity, slow growth, and renewal.…”
Section: Introductionmentioning
confidence: 99%